Analysis of hyperalgesia time courses in humans after painful electrical high-frequency stimulation identifies a possible transition from early to late LTP-like pain plasticity - Pfau, Doreen; Klein, Thomas; Putzer, Daniel; Pogatzki-Zahn, Esther M.; Treede, Rolf-Detlef; Magerl, Walter (Pain, 2011)
Electrical high-frequency stimulation (HFS) of skin afferents elicits long-term potentiation (LTP)-like hyperalgesia in humans. Time courses were evaluated in the facilitating (homotopic) or facilitated (heterotopic) pathways to delineate the relative contributions of early or late LTP-like pain plasticity. HFS in healthy subjects (n=55) elicited highly significant pain increases to electrical stimuli via the conditioning electrode (to 145% of control, homotopic pain LTP) and to pinprick stimuli in adjacent skin (to 190% of control, secondary hyperalgesia). Individual time courses in subjects expressing a sufficient magnitude of hyperalgesia (>20% pain increase, n=28) revealed similar half-lives of homotopic pain LTP and secondary hyperalgesia of 6.9 h and 4.9 h (log(10) mean 0.839±0.395 and 0.687±0.306) and times to full recovery of 48 h and 24 h (log(10) mean 1.679±0.790 and 1.373±0.611). Time course and peak magnitudes were not correlated between (r=-0.19to+0.21, NS), nor within both readout (r=0.29 and 0.31, NS). In most subjects, time courses were consistent with early LTP1. Notably, in some subjects (10 of 28), estimated times to full recovery were much longer (>10 days), possibly indicating development of late LTP2-like pain plasticity. Dynamic mechanical allodynia (only present in 16 of 55 subjects) lasted for a shorter time than secondary hyperalgesia. Three different readouts of nociceptive central sensitization suggest that brief intense nociceptive input elicits early LTP1 of pain sensation (based on posttranslational modifications), but susceptible subjects may already develop longer-lasting late LTP2 (based on transcriptional modifications). These findings support the hypothesis that LTP may contribute to the development of persistent pain disorders.
Gesehen am 08.12.2022